Automatic Modern Garbage System Collection - Mohammad Roszwan, Jamaudin (UTeM, 2010)
This project is about designing and developing a prototype of an automatic modem garbage system collection to make the process of collection garbage is convenience to use, less maintenance and less smell. The project proposed is fully automatic system which can reduce the time and power consumption. The automatic modem garbage system collection is fully automatic using Programmable Logic Controller as the controller for this project .The program is design is by using the eX-programmer and can be simulated based on the design. The automatically process starts from the inserting the garbage bag, then sealing and fmally arranges the bag automatically. The development of the hardware for this project is the most important part. The researching, designing and developing for the mechanism for the process need to be done properly so that the process can run as plans.